Rethinking the marginal:service design for development - Miettinen, Satu Anneli; Vuontisjärvi, Hanna-Riina Maria (2016)
This article is asking how service design can be used for development and improving livelihoods in the margin? The margin can be geographical but is can also be created around complex wicked problems that have resulted from historical or societal reasons. The article presents two cases studies where the margin is constructed around two different situations. The first case is looking at the arctic context of Lapland where geography causes marginalization and isolation. This case study is connected with “IKÄEHYT” project focusing on designing services with the elderly. The project was run in 14 Lappish communities to increase accessibility, inclusion and wellbeing. The second case is looking at indigenous San communities in South Africa where historical and societal context is creating a challenging situation for the local youth. The second case study is presenting ”PARTY” project (Participatory Development) with youth where service design is used to increase the youth participation in open democratic society and in designing their services. The article has a strong social design ethos. The article gives a brief overview on social design debates and uses that as a framework to analyze the case studies. Both case studies contribute to the rethinking of the marginal, how it is constructed and how service design can be used to create new solutions to overcome the challenges.